Avaliação da ativação plaquetária em pacientes com Diabetes Mellitus tipo 2 e sua associação com a resistência à insulina - Robalo, Silvino Sasso (2016)
The incidence of diabetes mellitus (DM) has increased, becoming a global public health problem. Approximately 415 million people worldwide have DM, causing chronic complications including changes in the state of blood homeostasis. In DM there are circulatory disorders caused by platelet hyperreactivity due to increased adhesion, activation and platelet aggregation, resulting in the release of the content of alpha granules, including β-thromboglobulin (βtg) and platelet-factor-4 (CXCL4), as well as thromboxane B2 (TxB2). Insulin resistance (IR) has been shown to predict DM and atherosclerosis, as well as cardiovascular diseases. One of the methods used for the evaluation of IR is through HOMA index (Homeostasis model assessment). This study aimed to verify changes in coagulation by determining the concentrations of fibrinogen, D-dimers and platelet activation (TxB2, βtg and CXCL4) and associate it with the HOMA model in newly diagnosed type 2 diabetic patients. We recruited 38 newly diagnosed and untreated patients with DM2 and 38 healthy subjects. These patients were stratified into the following HOMA quartiles: HOMA-1 (0.89 to 1.77), HOMA-2 (1.77 to 5.26), HOMA-3 (5.26 to 11.32) and HOMA-4 (11.32 to 18.56). Levels of fibrinogen and D-dimers were measured by immunoturbidimetric method, while TxB2, βtg and CXCL4 were quantified by ELISA technique according to the manufacturers’ recommended protocols. According to the results HOMA values were positively correlated with TxB2 (r = 0.75, p <0.001), βtg (r = 0.75, p <0.001), CXCL4 (r = 0.68, p <0.001), fibrinogen (r = 0.54, p <0.001) and D-dimer (r = 0.52, p <0.001). In addition, increased levels of these markers were observed in the higher HOMA quartiles. These findings suggest that patients newly diagnosed with diabetes have insulin resistance which is related to changes in blood homeostasis and the release of components of platelet granules capable of stimulating the cellular response that can cause atherosclerosis. In conclusion, it may be suggested that elevated levels of HOMA may serve as an alert for possible complications in blood homeostasis and lipid metabolism in newly diagnosed diabetic patients and that may cause future complications that will impact the quality of life of these patients.